IMPLEMENTASI PEMBELAJARAN BERDIFERENSIASI BAGI ABK RINGAN DI UPT SPF SD INPRES BIRA 2 MAKASSAR - Nadien Resqiana Suci; Wa Ode Mutia Nur; Aza Nur Faiza; Nur Wulandani; Dwiyatmi Sulasminah (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study aims to identify and describe the implementation of differentiated learning for students with mild special needs (ABK) at the SPF Unit of SD Inpres Bira 2 Makassar, a public elementary school facing limited resources. Amidst the absence of a Special Guidance Teacher (GPK) and limited supporting infrastructure, this study explores how classroom teachers adapt the curriculum to maintain an inclusive environment. The approach used is a qualitative descriptive case study with a single data collection technique through in-depth interviews. Data were analyzed using the interactive model of Miles, Huberman, and Saldana, which includes data reduction, data presentation, and conclusion drawing. The results show that differentiated learning is implemented through a “minimalist resilience” strategy. Teachers conduct sociocultural diagnostic assessments by identifying students’ financial and environmental backgrounds to map learning needs. In the process, the “Gotong Royong” (peer tutoring) strategy is utilized to manage a large class of 35 students, where high-ability students assist students with learning disabilities. In addition, content differentiation is carried out through the creation of concrete learning media from recycled materials, such as cardboard clocks, to facilitate visual and kinesthetic learning. Assessment is conducted adaptively, shifting the focus from rigid academic standards to individual and character development. This study concludes that the success of differentiated learning in inclusive environments depends more on pedagogical flexibility and the use of social capital than simply material facilities.